1989
DOI: 10.1111/j.1151-2916.1989.tb06301.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cation Exchange in Substituted Tobermorites

Abstract: Selective cation exchange in tobermorites with three levels of A13+ and Na+ substitution for Si4+ has been investigated. The cation exchange selectivity for a tobermorite with 2 mol% A13+ and 0 mol% Na+ substitution increased as follows:MgZf > Ba2+ > SrZ+. Cation exchange in the above tobermorite is postulated to take place mainly from edge and planar surface sites and apparently from interlayer Ca2+ sites. Tobermorites with 10 and 15 mol% A13+ (and Na+) substitution have additional Na' exchange sites in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…The negatively charged aluminosilicate surface sites thus formed, repel OH − ions and thus depress their attack on the silica structure [180,186]. Aluminum is known to interact with C-S-H to form the aluminummodified calcium silicate hydrate C-A-S-H. Komarneni and co-workers [187][188][189] demonstrated through NMR studies on tobermorite that Al was mainly found in C-S-H in tetrahedral coordination Al[IV] occurring in both Q2 and Q3 chain sites that linked across interlayers. They suggested that this linkage played an important role in cation exchange properties.…”
Section: Role Of Aluminummentioning
confidence: 96%
“…The negatively charged aluminosilicate surface sites thus formed, repel OH − ions and thus depress their attack on the silica structure [180,186]. Aluminum is known to interact with C-S-H to form the aluminummodified calcium silicate hydrate C-A-S-H. Komarneni and co-workers [187][188][189] demonstrated through NMR studies on tobermorite that Al was mainly found in C-S-H in tetrahedral coordination Al[IV] occurring in both Q2 and Q3 chain sites that linked across interlayers. They suggested that this linkage played an important role in cation exchange properties.…”
Section: Role Of Aluminummentioning
confidence: 96%
“…If a mixture of aluminium and sodium are substituted the sodium site can actas an additional exchange site. Then the cation selectivity changes from St 2+ < Ba 2+ < Mg 2+ to Mg 2+ < St 2+ < Ba 2+ [169].…”
Section: Layer Alun~osiheatesmentioning
confidence: 99%
“…However, the ion exchange selectivity for these ions has not been investigated, and the experimental conditions cannot be decided to obtain each ionic form. The present procedures were taken from our conventional method (Tsuji and Komarneni, 1989). Then the samples were washed with water to remove the excess Fe(CN)64-ions and air-dried.…”
Section: Conditioning O Fair-dried Products and Chemical Analysesmentioning
confidence: 99%
“…Recently, magnetiteintercalated mica has been found to show CO2 decomposition reactivity (Tsuji et al, 1993b). There exist a large number of layered compounds such as phosphates and tobermorite that are well known as cation exchangers or H20 adsorbers (Clearfield, 1988;Komarneni and Tsuji, 1989;Komarneni, 1989, 1991). Other layered compounds belonging to solid bases, such as hydrotalcite-like compounds(HT) and Al(OH)3-derived compounds, exhibit an anion-exchange property (Miyata, 1983;Sissoko et al, 1985).…”
Section: Introductionmentioning
confidence: 99%